Different relationships between the first 2 years on growth hormone treatment and the d3-growth hormone receptor polymorphism in short small-for-gestational-age (SGA) children - Dörr, Helmuth-Günther; Bettendorf, Markus; Hauffa, Berthold P.; Mehls, Otto; Rohrer, Tilman; Stahnke, Nikolaus; Pfäffle, Roland; Ranke, Michael B.; Group, for the German KIGS (Clinical endocrinology, 2011)
Background There has been controversy in recent years on whether the d3 polymorphism of the GH receptor is associated with a better growth response to GH in idiopathic short children born small for gestational age (SGA). Methods In this prospective study, we evaluated exon 3-GHR polymorphisms in 142 (62 f, 80 m) short prepubertal children born SGA (birth length and/or weight of ≤−2 SD for GA) and treated with rhGH (mean dose of 0·30 mg/kg/week) in 24 centres in Germany. A growth prediction for the first year of therapy was calculated for each child according to Ranke and co-workers. The index of responsiveness (IOR) was calculated by dividing the response (observed growth minus predicted growth) by the standard error of the prediction. All analyses were performed in one centre on samples collected and shipped on filter paper. The DNA fragment containing or missing exon 3 of the GHR was amplified by multiplex PCR. Results The fl-GHR isoform was most common with a frequency of 47·8%, followed by the d3/fl isoform with 38% and the d3-GHR isoform with 14·2%. There were no significant differences regarding gestational age, birth weight and birth length, mid parental height-SDS, chronological age at start of therapy, height-SDS, BMI-SDS, height velocity and GH dose between the different subgroups according to the genotype. After the first treatment year, height (H)-SDS (P < 0·05), height velocity (HV) (P < 0·01), HV-SDS (P < 0·001) and delta-H-SDS (P < 0·05) were significantly higher in patients with d3-GHR than in those with fl-GHR. The mean IOR was above 0 in children with at least one d3 allele, and highest, with 0·54, in those with the d3-GHR isoform. After the second year on GH, no differences between the different GHR-isoforms were found. Conclusions According to our results, the exon 3-deleted GHR explains the better growth response to GH only for the first and not for the second year.